Development of a UPLC-MS/MS Method for the Quantification of VS-5584 and Its Application in Pharmacokinetic Studies in Rats - Chunling Zhou; Xiaoxin Li; Aiping He; Tianzhu Liu; Jinmiao Tian; Meihua Jiang; Lina Fang (Journal of Analytical Methods in Chemistry)
VS-5584 is a small-molecular compound that showed equivalent activity against mTOR and all class I PI3K isoforms and demonstrated preclinical activity in diverse cancer cell lines and xenograft tumor model, and rational combination of VS-5584 and other target therapies achieved promising outcomes in oncology. In the present study, we established and validated a simple and sensitive UPLC-MS/MS method for the determination of VS-5584 in plasma samples. VS-5584 was separated via an Acquity UPLC BEH C18 column, with a mobile phase composed of acetonitrile and 0.2% formic acid in water (40 : 60). The calibration curve displayed a good linearity in the range of 1.0–1000 ng/mL, with satisfactory accuracy (−13.6% < RE% < 8.8%) and precision (CV%, less than 9.2%). The validated method was then applied to a pharmacokinetic study in rats. After administration of 10 mg/kg, VS-5584 was absorbed quickly and reached a peak concentration of 473.2 ± 72.0 ng/mL after 20 min. The established method allows for the quantification of VS-5584 in rat plasma in detail and can be utilized to successfully describe the pharmacokinetic profile of VS-5584.